The Effectiveness of Antidepressant Combined with Quranic CBT in Reducing Anxiety Level of Moslem Outpatient withh Anxiety Disorder in Sultan Agung Islamic Hospital in Semarang - Metrikana Novembrina; Dinia Eko Kusmianti Putri; Ferika Indrasari; Wahyu Setyaningsih (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2021)
Anxiety disorders is an emotional condition in which a person feels excessively anxious and it is generally caused by the excessive perception of a particular danger threatens the security of an individual and sometimes interferes with the daily activities and social interaction of an individual. This study aimed to determine the effectiveness of the Quranic CBT in reducing the anxiety level of the outpatient with anxiety disorder in Sultan Agung Islamic Hospital, Semarang. This was a treatment trial research using purposive sampling technique. In this study as much as 20 patients diagnosed with anxiety disorders and in the treatment with antidepressants were randomly divided into 2 groups. Group 1 was the patients undergoing therapy with antidepresant and also given Quranic CBT. Group 2 was the patients using antidepressant drugs and not given Quranic CBT therapy. This showed that the Quranic CBT method was effective in reducing the anxiety level.